Fulfilling Information Security Requirements at Polish Technical Universities in Empirical Research - Malgorzata WISNIEWSKA; Zbigniew WISNIEWSKI (Communications of International Proceedings, 2021)
The article presents the results of research conducted in Polish technical universities in the field of security of processed information. Conclusions are presented on the fulfillment of the requirements for organizing security, including coordinating information security, division of responsibility, use of information processing equipment, use of information security consulting, conducting cooperation with other organizations, ensuring security of third-party access, and security requirements in outsourcing contracts. The results of the study indicate that universities try to implement the principles of information security organization, but they do not recognize the relevance of some issues in this area, thus they interpret them incorrectly. This leads to serious negligence in information security.
Keywords: Information Systems; Information Security Management; Knowledge Management